PERBEDAAN RERATA KADAR MMP-2 ( MATRIX METALLOPROTEINASE - 2 ) DENGAN KETUBAN PECAH DINI PADA KEHAMILAN PRETERM DAN KEHAMILAN NORMAL - Sri Marlia (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
Premature rupture of membranes is the rupture of membranes prior to the onset of labor. Its found WHO data that 15% of pregnant women developed into complication one of the causes is premature rupture of membranes. MMP-2 is part of the matrix metalloproteinase which is an enzyme that breaks down collagen in which collagen provides the main strain force on fetal membranes. This study aimed to know the differences of Matrix Metalloproteinase 2 (MMP-2) between premature rupture of membranes on preterm pregnancy and normal pregnancy. Research design was cross sectional comparative study. The sample in this study were pregnant women with premature rupture of membranes on preterm pregnancy before 37 weeks and women with normal pregnancy. MMP-2 levels examination using Human MMP2 ELISA kit. Data analyze with independent sample t test. The results showed that the mean of MMP-2 levels in premature rupture of membranes on preterm pregnancy was 16.06 ± 6.33 ng/ ml higher than the normal pregnancy of 9.86 ± 4.45 ng / ml. The result of statistical test obtained p value =0.003 (p value <0,05). There is difference of MMP-2 serum level on premature rupture of membranes preterm pregnancy and normal pregnancy. This research concluded there is difference of MMP-2 serum level on premature rupture of membranes preterm pregnancy and normal pregnancy. Keywords : MMP-2, rupture of membranes, preterm pregnancy